Nightwork eaudiobook A novel. - Roberts, Nora (Macmillan Audio, 2022)
#1 New York Times bestselling author Nora Roberts introduces an unforgettable thief in an unputdownable new novel... Greed. Desire. Obsession. Revenge . . . It's all in a night's work. Harry Booth started stealing at nine to keep a roof over his ailing mother's head, slipping into luxurious, empty homes at night to find items he could trade for precious cash. When his mother finally succumbed to cancer, he left Chicago—but kept up his nightwork, developing into a master thief with a code of honor and an expertise in not attracting attention—or getting attached. Until he meets Miranda Emerson, and the powerful bond between them upends all his rules. But along the way, Booth has made some dangerous associations, including the ruthless Carter LaPorte, who sees Booth as a tool he controls for his own profit. Knowing LaPorte will leverage any personal connection, Booth abandons Miranda for her own safety—cruelly, with no explanation—and disappears. But the bond between Miranda and Booth is too strong, pulling them inexorably back together. Now Booth must face LaPorte, to truly free himself and Miranda once and for all. A Macmillan Audio production from St. Martin's Press.